Ultrastructural Analysis of Rehydrated Human Donor Corneas After Air-Drying and Dissection by Femtosecond Laser - Pedrotti, Emilio; Bonacci, Erika; Fasolo, Adriano; De Rossi, Arianna; Camposampiero, Davide; Jones, Gary L. A.; Bernardi, Paolo; Merigo, Flavia; Ponzin, Diego; Marchini, Giorgio; Sbarbati, Andrea (Frontiers in Medicine, 2021)
Purpose: To evaluate the efficiency of femtosecond laser (FSL) incision of rehydrated human donor corneas after air-drying and its effects on corneal structure. Methods: We compared the rehydrated and fresh-preserved corneas by microscopy following Victus-Tecnolas FSL treatment for straight-edge anterior lamellar keratoplasty (ALK). The corneas were dehydrated at room temperature under a laminar-flow hood. Results: To obtain the horizontal cut in rehydrated corneas, we increased the FSL pulse energy to 1.2 μJ from 0.80 μJ applied for the fresh corneas and obtained a clear-cut separation of the lamellar lenticule cap from the corneal bed. Light microscopy showed regular arrangement of stromal collagen lamellae, with spaces in between the fibers in the corneal stroma in the fresh and the rehydrated corneas, but the uppermost epithelial layers in the rehydrated corneas were lost. Transmission electron microscopy (TEM) revealed no signs of thermal or mechanical damage to the corneal structure. The epithelial basal membrane and Bowman's layer maintained their integrity. The epithelial basal layer and cells were separated by large spaces due to junction alteration in the rehydrated corneas. There were gaps between the lamellar layers in the stroma, especially in the rehydrated corneas. Keratocytes displayed normal structure in the fresh corneas but were devoid of microorganules in the rehydrated corneas. Minor irregularities were observed in the vertical incision and the horizontal stroma appeared smooth on scanning electron microscopy. Conclusion: The corneal stroma of rehydrated corneas maintained morphology and integrity, while corneal cellular components were generally altered. When corneas are intended for FSL-assisted ALK, effective stromal bed incision is best achieved at a laser power higher than that currently adopted for fresh corneas.